Dermoscopy of nail fold and elbow in the differential diagnosis of early psoriatic arthritis sine psoriasis and early rheumatoid arthritis. Issue 10 (5th October 2016) - Errichetti, Enzo; Zabotti, Alen; Stinco, Giuseppe; Quartuccio, Luca; Sacco, Stefania; De Marchi, Ginevra; Piccirillo, Angelo; De Vita, Salvatore
Abstract: Differentiation between psoriatic arthritis (PsA) sine psoriasis and rheumatoid arthritis (RA) may be a challenge, especially in the early stages, hence the need for new instrumental markers to assist their diagnosis. In this study, we investigated possible dermoscopic differences in vascular appearance of nail fold and elbow (a classic site of repeated trauma) in these two conditions. Fifteen patients with PsA sine psoriasis, 12 patients with RA and 12 controls were included in the study. Regarding the nail fold vascular appearance in PsA sine psoriasis and RA cohorts, the presence of diffuse reddish background with or without sparse dotted vessels was significant in the former, whereas the evidence of parallel dotted/short linear vessels ("fish school‐like" pattern) or irregular/ramified, blurry, purple vessels were significant in the latter; none of these patterns were detected in the control group. Regarding the elbow, the pattern significantly associated with PsA sine psoriasis consisted of diffusely distributed, red, dotted vessels. On the other hand, RA patients and controls displayed similar dermoscopic findings, with three possible vascular patterns being observed: (i) irregular, blurry, purple vessels; (ii) avascular appearance; and (iii) sparse, dotted, purple vessels. In conclusion, dermoscopy may be a useful supportive tool for differentiating early PsA sine psoriasis from RA.